Delayed Release of Neurotransmitter from Cerebellar Granule Cells - Atluri, Pradeep P. (J Neurosci, 1998)
At fast chemical synapses the rapid release of neurotransmitter that occurs within a few milliseconds of an action potential is followed by a more sustained elevation of release probability, known as delayed release. Here we characterize the role of calcium in delayed release and test the hypothesis that facilitation and delayed release share a common mechanism. Synapses between cerebellar granule cells and their postsynaptic targets, stellate cells and Purkinje cells, were studied in rat brain slices. Presynaptic calcium transients were measured with calcium-sensitive fluorophores, and delayed release was detected with whole-cell recordings. Calcium influx, presynaptic calcium dynamics, and the number of stimulus pulses were altered to assess their effect on delayed release and facilitation. Following single stimuli, delayed release can be separated into two components: one lasting for tens of milliseconds that is steeply calcium-dependent, the other lasting for hundreds of milliseconds that is driven by low levels of calcium with a nearly linear calcium dependence. The amplitude, calcium dependence, and magnitude of delayed release do not correspond to those of facilitation, indicating that these processes are not simple reflections of a shared mechanism. The steep calcium dependence of delayed release, combined with the large calcium transients observed in these presynaptic terminals, suggests that for physiological conditions delayed release provides a way for cells to influence their postsynaptic targets long after their own action potential activity has subsided.